Habitat Preferences, Distribution Pattern, and Root Weight Estimation of Pasak Bumi (Eurycoma longifolia Jack.) - Siti Masitoh Kartikawati; Ervizal Amir Muhammad Zuhud; Agus Hikmat; Hariadi Kartodihardjo; Munawar Fuadi (Institut Pertanian Bogor (IPB University), 2014)
Pasak bumi (Eurycoma longifolia Jack) is one of non timber forest products with “indeterminate” conservation status and commercially traded in West Kalimantan. The research objective was to determine the potential of pasak bumi root per hectare and its ecological condition under natural habitat. Root weight of E. longifolia Jack was estimated using simple linear regression and exponential equation with stem diameter and height as independent variables. The results showed that the individual number of the population was 114 with the majority in seedling stage with 71 individuals (62.28%). The distribution was found in clumped pattern. Conditions of the habitat could be described as follows: daily average temperature of 25.6oC, daily average relative humidity of 73.6%, light intensity of 0.9 klx, and red-yellow podsolic soil with texture ranged from clay to sandy clay. The selected estimator model for E. longifolia Jack root weight used exponential equation with stem height as independent variable using the equation of Y= 21.99T0,010 and determination coefficient of 0.97. After height variable was added, the potential of E. longifolia Jack minimum root weight that could be harvested per hectare was 0.33 kg.